Distribution and source rock potential of the Chattanooga shale in Kansas - McColloch, Austin (Kansas State University, 2016)
Organic-rich shales were deposited over a large part of what is now North America during the Late Devonian. North America in the late Devonian was located in the tropics (Woodrow et al., 1973), possibly in low southerly latitudes (Heckel and Witzke, 1979; Witzke and Heckel, 1988; Streel et al., 1990). This environment creates an organic-rich environment that resulted in thick, black shales. The Devonian-Mississippian Chattanooga (Woodford) shale is known to be an important petroleum source rock in many intracratonic basins of the Midcontinent (Lambert, 1993). Geochemical analysis of the Chattanooga shale, using various techniques, provides additional information on oil-source rock potential. Handheld XRF analysis was conducted on well cuttings samples, Loss on Ignition (LOI) was performed on a subset of those samples and mapping of the organic matter results of the two methods was completed. Handheld XRF still has the prospect for providing quick analysis to infer organic matter content to be used as a determination of the quality of source rock. Although slightly reduced correlation has been found within this study compared to Willey (2015), the method has still proven viable for fracking targets to be determined on site and in a more efficient manner. Loss on Ignition results have correlated with TOC data better then XRF results, making this method the better option for evaluating source rock potential. Mapping of these results provide the first known source rock potential map across Kansas and can be used by the industry for future exploration.
Keywords: Geology; Chattanooga Shale; Total Organic Carbon; Handheld X-Ray Fluorescence; Geochemistry (0996); Geology (0372); Petroleum Geology (0583)